2018
DOI: 10.1016/j.worlddev.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Household Income and Child Nutrition Outcomes Evidence from Uganda

Abstract: HighlightsThis study takes advantage of income and height measurements from three years of the Uganda National Panel Survey.No correlation of short-term changes in income and height measures overall but small positive correlation for younger kids.Compared to wages, only share of income from nonfarm self-employment correlates positively with HAZ in the sector analysis.In agriculture, income shares from (i) consumption of own crops and (ii) low-protein crop production show negative effects.Overall, any effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
3
23
2
2
Order By: Relevance
“…Enhancing agricultural productivity can also improve food security (Dizon et al, 2019). However, the link between agricultural growth and food security is less clear (Kirk et al, 2018).…”
Section: Malnutrition and Food Securitymentioning
confidence: 99%
“…Enhancing agricultural productivity can also improve food security (Dizon et al, 2019). However, the link between agricultural growth and food security is less clear (Kirk et al, 2018).…”
Section: Malnutrition and Food Securitymentioning
confidence: 99%
“…Income was captured in terms of total household income per month. The main sources of household income were also included, as literature has shown that incomes from different sources are spent varyingly across household needs [50,51]. The household's wealth status was also captured.…”
Section: Measurement Of Key Variablesmentioning
confidence: 99%
“…Boosting agricultural output in a country can also improve food security and nutrition. But the global evidence on this is sparse, and the link between agricultural growth and nutrition is less clear (Kirk, Kilic, and Carletto 2018).…”
Section: Agricultural Growth and Productivitymentioning
confidence: 99%